2022
DOI: 10.1111/grs.12392
|View full text |Cite
|
Sign up to set email alerts
|

GR24 alleviates the adverse effects of drought stress on physiology and photosystem II function in alfalfa (Medicago Sativa L.)

Abstract: Drought is a major environmental stress that limits growth and development of plants.Strigolactone, a kind of carotenoid-derived sesquiterpenoid hormone, plays an important role in resisting abiotic stress for plants. In this study, alfalfa (Medicago Sativa L.) WL-712 was sprayed with GR24 (a synthetic strigolactone analog) at the concentration of 0.1 μM for 3 days under drought stress for 1 week. The results showed that GR24 treatment could increase the contents of soluble protein and soluble sugar and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Chlorophyll serves as the fundamental basis for photosynthesis, and alterations in chlorophyll content play a pivotal role in evaluating plant growth and drought tolerance. Previous studies have demonstrated that SLs enhance chlorophyll content under drought stress in various crops, including wheat [21], maize [31], rapeseed [32], grape [33], and alfalfa [34]. In this study, we observed a decrease in chlorophyll content (chlorophyll a, chlorophyll b, total chlorophyll, and SPAD value) under drought conditions; however, priming with SLs significantly increased these indices under drought stress (Figure S4).…”
Section: Sls Restrained Degradation Of Chlorophylls and Increased Bio...supporting
confidence: 40%
See 1 more Smart Citation
“…Chlorophyll serves as the fundamental basis for photosynthesis, and alterations in chlorophyll content play a pivotal role in evaluating plant growth and drought tolerance. Previous studies have demonstrated that SLs enhance chlorophyll content under drought stress in various crops, including wheat [21], maize [31], rapeseed [32], grape [33], and alfalfa [34]. In this study, we observed a decrease in chlorophyll content (chlorophyll a, chlorophyll b, total chlorophyll, and SPAD value) under drought conditions; however, priming with SLs significantly increased these indices under drought stress (Figure S4).…”
Section: Sls Restrained Degradation Of Chlorophylls and Increased Bio...supporting
confidence: 40%
“…The improvement of leaf water relations could increase Pn in wheat under drought stress [37]. Interestingly, application of SLs has been demonstrated to enhance photosynthetic performance under drought conditions [19,32,34,38,39]. In this study, SLs priming could increase antioxidant activity to scavenge excess ROS, improve leaf water relations, and enhance chlorophyll content under drought stress; these changes led to the improvement of photosynthetic performance (Pn, Tr, and Gs), and then increased root and shoot biomass (Figures 1-3, S3 and S4).…”
Section: Sls Promoted Photosynthesis By Increasing Electron Transport...mentioning
confidence: 99%